Poesia, divinazione, menzogna. Friedrich Nietzsche sull’origine della poesia - Gentili, Carlo (Bollettino Filosofico, 2017)
Nietzsche’s thinking is always characterised by a constant dialogue with poetry and its themes. The first edition of the Gay Science presents in fact at the beginning a collection of epigrams (Joke, Cunning and Revenge) and an important aphorism, On the Origin of Poetry (n. 84), whose analysis will be the object of this contribution. The paper aims therefore to demonstrate that poetry, despite having a religious origin, is for Nietzsche a form of instrumental fiction, because it binds, it forces through a sort of «compulsion» (Zwang) the divinity to the fixed terms of rhythm. Consequently, the contribution points out that poetry is for Nietzsche the form of lie par excellence. In order to remark that poetry and philosophy are intertwined, the paper will finally show that for Nietzsche the lie is in a close relationship with truth.